Grave of Karl, his wife Jenny, his grandson Harry and his housekeeper Helena Demuth. Graveyard Highgate, London. Before the erection of the Marx-statue in 1956. The Marx-grave: with flowers
Grave of Karl, his wife Jenny, his grandson Harry and his housekeeper Helena Demuth. Graveyard Highgate, London. Before the erection of the Marx-statue in 1956. The Marx-grave: with flowers.